Pengaruh Pemberian Nebulizer Dan Deep Breating Exercise Terhadap Perubahan Saturasi Oksigen Pada Pasien PPOK Di RS Paru Jember - Moh Mujibus Sauqi; Angria Pradita; Rachma Putri Kasimbara; Nurul Halimah (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2023)
Chronic Obstructive Pulmonary Disease (COPD) is a respiratory disease indicated by airflow limitation due to airway abnormalities. COPD patients are identical with airway obstruction or decreased lung function to carry out the exchange of oxygen and carbon dioxide which is characterized by cyanosis, hypoxemia, decreased concentration and mood changes. This condition results in a decrease in oxygen saturation which causes the percentage of hemoglobin and oxygen binding in the arteries to decrease to <85 %. One of the treatments used in COPD patients is the administration of a nebulizer and deep breathing exercise. This study aims to identify the effect of giving a nebulizer and deep breathing exercise to changes in oxygen saturation of COPD patients. This study has 20 respondents using a sampling technique that is purposive sampling. This research design uses a quasi-experimental type with a one group pretest and posttest approach. Bivariate analysis in this study using Paired T Test. The results of this study are the average oxygen saturation before giving a nebulizer and deep breathing to COPD patients is 92.70, the average oxygen saturation after giving a nebulizer and deep breathing to COPD patients at Jember Lung Hospital is 94.05, and there is an effect of giving a nebulizer and deep breathing to changes in oxygen saturation of COPD patients at Jember Lung Hospital with p-value = 0.001 (p<0.05). This research is expected to be an input for additional information based on data and theory to improve the quality of physiotherapy services by making standard procedures in performing nebulizers and deep breathing, especially in COPD patients